Rearticulating Values Through Applied Theories at Children's Hospital Colorado. (August 2013) - Wukitsch, Michael; Simmons, Ryan; Hutt, Mark
The Problem: A large, academically affiliated pediatric institution experienced a period of dramatic change leading to concerns of cultural fragmentation and a loss of shared cultural values. The Solution: An intervention was crafted using theories of action learning, appreciative inquiry (AI), and Scharmer's (2009) Theory U to reformulate organizational values. A project team representing different departments and organizational levels was created to develop a new values statement. The team facilitated staff listening sessions, distilled perspectives into themes, and synthesized the themes. A traditional values statement was replaced with a unique and original credo. The intervention demonstrates a unique approach to applying multiple theories to an organizational culture change effort. The Stakeholders: Human resource development (HRD) practitioners and scholars who are interested in the application of theory to interventions in an organizational context.